PERBEDAAN UTAMA PENGGUNAAN KAPURDAN SEMEN UNTUK BAHAN STABILISASI TANAH - Siegfried Siegfried; Nyoman Suaryana; Haliena Armela (Jurnal Jalan-Jembatan, 2005)
With the lack of availability of natural resources will alse affect to the road construction and maintenance process. This problem can be solved by improving the quality of material that is available near the road locations. that is the reason to implement the technologies that can improve the quality of materials which is considering some aspect namely material types, material deposits, and also the level of successful in the past. One of such technologied is the soil stabilization which is using lime and cement as the stabilizing agents. The main difference between these two kinds of stabilization is its use for a certain type of soil. The use of lime is suitable for the soils whose PI more than 10% while cement is more applicable for fine grained soils if the PI less than 10% and also for the coarse grained soils (less than 25% passing sieve No. 200). Lime stabilization will increase the bearing capacitty of soils and reduce plasticity and swelling. The succesful of road stabilization is influenced by several factors such as (i) the selection of stabilizing agent that suits to type of soils, (ii) the accuracyof mix desihn, (iii) the level of mixing and compaction in the field , and (iv) the maintenance process durig curing time.